(±)-Camphor sulfonic acid assisted IBX based oxidation of 1° and 2° alcohols. (28th September 2021) - Kumar, Kamlesh; Joshi, Penny; Rawat, Diwan S
Graphical abstract: Highlights: Efficient methodology has been developed for the oxidation of primary and secondary alcohols using IBX-Camphor sulfonic acid catalytic system. The methodology is compatible with a variety of substrates having arene, heteroarene and alkene functionalities. The reaction works well in the binary solvent system.